Pengelolaan Aset Tetap BUMDes melalui Sistem Perhitungan Penyusutan Aset Tetap - Ni Luh De Erik Trisnawti; Gede Oktha Prastyawan (STEKOM PRESS, 2024)
Problems regarding the imposition of depreciation values ​​and the presentation of fixed assets in financial reports still frequently occur. Charging depreciation costs that are too high has an impact on decreasing company profits, but conversely, charging depreciation costs that are too low results in increasing company profits. This research aims to assist in designing a fixed asset depreciation system BUMDes. The research began by analyzing the problems faced regarding the need for a depreciation system, as an effort to manage fixed assets. The researchers designed a system for calculating depreciation of fixed assets and implementing it in managing fixed assets. The research results show that the design of this depreciation system is very helpful in providing convenience for BUMDes. Fixed assets on the balance sheet can also be presented at their book value in accordance with accounting standards for the presentation of fixed assets.